Transcriptomic Characterization of Male Formosan Pangolin (Manis pentadactyla pentadactyla) Reproductive Tract and Evaluation of Domestic Cat (Felis catus) as a Potential Model Species - Méar, Laura Orama; Tseng, IShin; Lin, Kuei-Shien; Hsu, Chia-Lin; Chen, Szu-Hua; Tsai, Pei-Shiue (Animals (Basel), 2024)
The Formosan pangolin (Manis pentadactyla pentadactyla) is an endemic animal of Taiwan. Due to their reduced population and behavior, very little is known about this enigmatic species. To unravel male pangolin reproduction, in the present study, we built a complete genomic database of the male Formosan pangolin reproductive tract and revealed highly expressing genes as well as critical signaling pathways and their associated biological processes in both the testis and the epididymis. Moreover, we evaluated the domestic cat (Felis catus) as a potential model species for male pangolin reproduction by comparing their testicular transcriptomes. We demonstrated a clear tissue-specific gene expression supporting the unique biological signature of each reproductive tissue and identified critical genes of the different reproductive organs. Pathway enrichment analysis revealed unique pathways in the testis as well as a clear epididymal transition. Furthermore, domestic cats, despite being the closest domestic species to pangolin, demonstrated their unfitness as a male reproduction model species as clear differences in spermatid differentiation and metabolism were observed. These results enable a better understanding of male pangolin reproduction characteristics and may inspire improvements in in Formosan pangolin conservation strategies.